Histone Lysine Methylation and Long Non-Coding RNA: The New Target Players in Skeletal Muscle Cell Regeneration - Mbadhi, Magdaleena Naemi; Tang, Jun-ming; Zhang, Jing-xuan (Frontiers in Cell and Developmental Biology, 2021)
Satellite stem cell availability and high regenerative capacity have made them an ideal therapeutic approach for muscular dystrophies and neuromuscular diseases. Adult satellite stem cells remain in a quiescent state and become activated upon muscular injury. A series of molecular mechanisms succeed under the control of epigenetic regulation and various myogenic regulatory transcription factors (MRFs), leading to their differentiation into skeletal muscles. The regulation of MRFs via various epigenetic factors, including DNA methylation, histone modification, and non-coding RNA, determine the fate of myogenesis. Furthermore, the development of histone deacetylation inhibitors (HDACi) has shown promising benefits in their use in clinical trials of muscular diseases. However, the complete application of using satellite stem cells in the clinic is still not achieved. While therapeutic advancements in the use of HDACi in clinical trials have emerged, histone methylation modulations and the long non-coding RNA (lncRNA) are still under study. A comprehensive understanding of these other significant epigenetic modulations is still incomplete. This review aims to discuss some of the current studies on these two significant epigenetic modulations, histone methylation and lncRNA, as potential epigenetic targets in skeletal muscle regeneration. Understanding the mechanisms that initiate myoblast differentiation from its proliferative state to generate new muscle fibres will provide valuable information to advance the field of regenerative medicine and stem cell transplant.